Supplying resilience through assessing diversity of responses to disruption. Issue 3 (21st February 2020) - Kahiluoto, Helena; Mäkinen, Hanna; Kaseva, Janne
Abstract : Purpose: The purpose of this paper is to contribute to the theory and practice of supply chain management in terms of how an organisation should structure its supply base to be resilient to supply uncertainties and disruptions. An empirical assessment of supplier response diversity is demonstrated, and the following research question posed: Is response diversity of suppliers positively associated with supply chain resilience, more positively than mere supplier diversity is? Design/Methodology/Approach: Resilience is operationalised as the maintenance of sales of two food products in 27 southern Finnish retail stores during two distinct disruptions. Response diversity is operationalised as 1) diversity in the personnel sizes of slaughterhouse suppliers of pork under domestic strikes and as 2) evenness in the proportions of imports and domestic supply of food oil under global price volatility. A five-step quantitative assessment is performed. Findings: Response diversity is positively related to the maintenance of sales, more positively than diversity of individual suppliers is. Research limitations/Implications: Response diversity is an advancement to the theory of supply chain resilience and supply base management, and access to big data increases practical potential. Practical implications: Empirical assessments of response diversity of suppliers provide buyer companies an effective means to enhance their supply base management for resilience. Social implications: The proposed approach is useful for teaching and for authorities to enhance food security. Originality/value: This first assessment of response diversity of supply chain operations presents an important advancement in the theory and practice of supply base management for resilience.